The magnetic anisotropy of field-assisted 3D printed nylon strontium ferrite composites - Mandesh Khadka; Oluwasola K. Arigbabowo; Jitendra S. Tate; Wilhelmus J. Geerts (AIP Advances, 2024)
Magnetic Field Assisted Additive Manufacturing (MFAAM), 3D printing in a magnetic field, has the potential to fabricate high magnetic strength anisotropic bonded magnets. Here, 10, 35, and 54 wt% strontium ferrite bonded magnets using polyamide 12 binder were developed by twin screw compounding process and then printed via MFAAM samples in zero, and in 0.5 Tesla (H parallel to the print direction and print bed). The hysteresis curves were measured using a MicroSense EZ9 Vibrating Sample Magnetometer (VSM) for 3 different mount orientations of the sample on the sample holder to explore the magnetic anisotropy. The samples printed in zero field exhibited a weak anisotropy with an easy axis perpendicular to the print direction. This anisotropy is caused by the effect of shear flow on the orientation of the magnetic platelets in the 3D printer head. For the MFAAM samples, the S values are largest along the print bed normal. This anisotropy is caused by the field. The alignment of the magnetic particles happens when the molten suspension is in the extruder. When the material is printed, it is folded over on the print bed and its easy axis rotates 90° parallel to the print bed normally. Little realignment of the particles happens after it is printed, suggesting a sharp drop in temperature once the composite touches the print bed, indicating that field-induced effects in the nozzle dominate the anisotropy of MFAAM deposited samples.